Proposed Model for Interference Estimation in Code Division Multiple Access - Dalal Kanaan Taher; Adheed Hassan Sallomi (Universitas Ahmad Dahlan, 2018)
Cellular CDMA systems are usually affected by interference experienced by users in adjacent cells that decrease the Quality of Services in wireless communication network. Hence, interference is the limiting factor of capacity in CDMA cellular and it is one of the problems fighting against the high efficiency of any mobile network. In this paper, a mathematical model to estimate the average number of users contributing in inter-cell interference at the busy hours of CDMA network is proposed. As the power exponent value has significant affect on interferer signal attenuation and hence other-cells interference, measurements were carried through a drive test to determine the received power level at various distance from CDMA base stations at Baghdad. The results obtained show that the power exponent was 2.71. This value was applied in dual-slop path loss model to determine the expected interference factor, and the number of users that can be hold at each cell. Simulations showed that users at a boundary cell generate more interference than those close to the base station. Furthermore, it was denoted that greater number of users caused to increase the interference factor, and greater power exponent value result in interference factor reduction.